Emotional labour in medicine - Vedi, Priyanka (2021)
The emotional workplace has been explored through several perspectives (e.g. Hochschild, 1983; Bolton, 2005) and within several different contexts (e.g. James, 1992; Ashforth and Humphrey, 1993; Morris and Feldman, 1996; Fineman, 2003; Ward and McMurray, 2016). Although several contributions exist on emotions within organisations, missing from these debates is the exploration of how institutional logics shape the performance and management of emotional labour on the frontline. There is also limited knowledge on how workers navigate their emotional labour process in light of heterogeneous logics. In this light, both Hochschild’s (1983) and Bolton’s (2005) analyses have been considered and extended in order to re-ignite debates of the emotional workplace. This thesis examines whether a lens provided by the institutional logics perspective develops our understanding of emotional labour by showing how competing institutional forces can be considered as shaping emotional aspects of work.